Experimental investigation and molecular dynamics simulations of plasma treatment on the interface strength of overmolded hybrid fiber reinforced polypropylene composites. Issue 3 (17th January 2022) - Tang, Huaping; Shi, Wuping; Ding, Yudong; Miao, Tianyu; Fu, Liang; Zhou, Mingyong; Zhai, Zhanyu
Abstract: Overmolded hybrid fiber reinforced thermoplastic composites (hybrid thermoplastic composites) composed of continuous fiber and short fiber reinforcement benefit from high mechanical performance, geometric complexity as well as low production cycle times. The effective bonding of continuous fiber reinforced part and injection molding compounds plays a vital role in controlling the mechanical performance of hybrid composites. In this present work, plasma treatment was applied on continuous fiber reinforced polypropylene composites laminate for increasing interface strength of hybrid composites. The effect of the plasma treatment was studied through experiments and molecular dynamics (MD) simulation. The results show that plasma treatment increases the interface strength of hybrid composites because of the generation of polar groups of OH, COOH, and NH2 . The contribution of each aspect to the improved interface strength was quantified by MD simulation. It is found that these active functional groups can promote the diffusion coefficient at interface. Moreover, the introduction of NH2 is more likely to enhance the bonding strength from the perspective of generated interaction energy at the interface. Abstract :